Stocking density in lambari alevinos Astyanax sp. in net tanks (Research, Society and Development, 2021)
The determination of stocking density is an essential parameter for the species under cultivation, especially in intensive production systems such as net tanks. In order to evaluate the influence of stocking density on the development of lambari fingerlings (Astianax sp.), Created in net tanks in the Itaipu Binacional Hydroelectric Reservoir, 20,000 fingerlings (0.95 ± 0.49g) and length (3.94 ± 0.65cm), were distributed in 20 net tanks (1 m³) with five stocking densities (400, 700, 1000, 1300, and 1600 fish / m3) and four replications. The fish were fed twice a day (8 am and 5 pm) with micro-extruded feed (0.8 to 1.2 mm) containing 42% crude protein. The physical-chemical parameters of the water were recorded daily and biometrics were performed weekly to correct the amount of feed to the fish. An inversely proportional linear effect of the stocking density on the final weight was observed, and a linear effect directly proportional for the final biomass, feed consumption and apparent feed conversion. There were no influences (P